GREAT SCHOLARS OF IX-XII CENTURIES INMOVAROUNNAHR AND KHORASAN (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the influential scholars of the 9th to 12th centuries in the regions of Movarounnahr and Khurasan. The author delves into the intellectual achievements and contributions of these great minds, highlighting their impact on various fields such as science, philosophy, and literature during this period. Through a detailed examination of their works and influence, the article sheds light on the cultural and academic landscape of Movarounnahr and Khurasan during this golden age of scholarship. By examining the lives and legacies of these scholars, readers gain a deeper understanding of the rich history and intellectual heritage of these regions.